Physical principles for scalable neural recording - Marblestone*, Adam H.; Zamft*, Bradley M.; Maguire, Yael G.; Shapiro, Mikhail G.; Cybulski, Thaddeus R.; Glaser, Joshua I.; Amodei, Dario; Stranges, P. Benjamin; Kalhor, Reza; Dalrymple, David A.; Seo, Dongjin; Alon, Elad; et al. (Frontiers in Computational Neuroscience, 2013)
Simultaneously measuring the activities of all neurons in a mammalian brain at millisecond resolution is a challenge beyond the limits of existing techniques in neuroscience. Entirely new approaches may be required, motivating an analysis of the fundamental physical constraints on the problem. We outline the physical principles governing brain activity mapping using optical, electrical,magnetic resonance, and molecular modalities of neural recording. Focusing on the mouse brain, we analyze the scalability of each method, concentrating on the limitations imposed by spatiotemporal resolution, energy dissipation, and volume displacement. We also study the physics of powering and communicating with microscale devices embedded in brain tissue.